The Unfortunate Event - Extramedullary Myeloma Of The Urinary Tract - Woo, W; Fei , L; Jagwani, A; Sabri, A (British Journal Of Surgical Science, 2023)
Multiple myeloma is a type of haematological malignancy that arises from the abnormal prolifera- tion of plasma cells leading to excessive production of monoclonal immunoglobulins ( 1). These antibody-secreting plasma cells are produced by the B-lymphocytes ( 2). They play an important role in humoral immune response due to their ability to produce antibodies. As important as the plasma cells are to the human body, they can be equally destructive in plasma cell neoplasms. Multiple myeloma is the more commonly known name for plasma cell neoplasm which is an um- brella term for a host of other disorders that are associated with clonal proliferation of plasma cells which includes extramedullary myeloma. We would like to discuss a rare case of extramedullary myeloma of the urinary tract in a 65 years old gentleman.